Contrasting effects of nitrogen deposition and increased precipitation on soil nematode communities in a temperate forest. (September 2020) - Liu, Tao; Mao, Peng; Shi, Leilei; Wang, Zuyan; Wang, Xiaoli; He, Xinxing; Tao, Libin; Liu, Zhanfeng; Zhou, Lixia; Shao, Yuanhu; Fu, Shenglei
Abstract: Elevated nitrogen (N) deposition and increased precipitation often occur simultaneously, and have an interactive effect on terrestrial ecosystems, particularly in N-limited temperate forests. However, the effects of interactions between elevated N deposition and increased precipitation on soil communities are unclear. In the present study, we employed a novel approach to simulate N deposition and precipitation by applying N solution and water to the forest canopy, and explored how throughfall chemical properties and soil nematode communities responded to elevated N deposition and increased precipitation. We found that N deposition positively affected nematode communities by increasing the abundance of nematodes in some bacterivorous and fungivorous nematode groups. In contrast, increased precipitation suppressed bacterivorous and fungivorous nematodes, particularly of those guilds related to nutrient enrichment. Our results suggest that the positive effects of N deposition on nematode communities may be cancelled out by increased precipitation in temperate forest ecosystems, when elevated N deposition and increased precipitation occur simultaneously. This was not observed in previous studies simulating N deposition and precipitation, which was probably due to that they have been mostly based on understory manipulation without considering canopy processes. Highlights: Precipitation and N deposition have a synergistic effect on forest ecosystems. Canopy processes must be considered in N deposition and precipitation study. Canopy N addition increases the abundance of soil microbial-feeding nematodes. Increased precipitation negatively affects the soil nematode community. Increased precipitation cancels out the effects of N deposition on soil nematodes.